Pengaruh Model Realistic Mathematics Education (RME) Terhadap Kemampuan Pemecahan Masalah Matematika Sekolah Dasar - Muntheawati, Niken; Arrahim, Arrahim; Safitri Mujiani, Dwi (ELSE (Elementary School Education Journal) : Jurnal Pendidikan dan Pembelajaran Sekolah Dasar, 2025)
The problem-solving ability of fourth-grade students in solving area measurement word problems remains low, as indicated by their difficulties in applying appropriate problem-solving procedures. This study aims to evaluate the problem-solving skills of fourth-grade students at SDN Duren Jaya IV, Bekasi City, by implementing the Realistic Mathematics Education (RME) model. A quasi-experimental research method was used with a non-equivalent pretest-posttest control group design. Validated instruments were employed to gather data for this research. Data processing and analysis were carried out using descriptive and inferential statistical methods. The results of the classroom experiment indicate that applying the Realistic Mathematics Education (RME) model positively impacts students' mathematical problem-solving abilities, especially in solving word problems. The findings proved that the group experimental achieved a mean score on the pretest of 42.76 and a posttest result of 80.00, while the control group improved from an average pretest score of 40.00 to a posttest score of 72.62. These findings highlight the importance of implementing the Realistic Mathematics Education (RME) model to enhance the problem-solving skills of fourth-grade students.